Local Irradiation Modulates the Pharmacokinetics of Metabolites in 5-Fluorouracil—Radiotherapy–Pharmacokinetics Phenomenon - Liu, Ju-Han; Tsai, Tung-Hu; Chen, Yu-Jen; Wang, Li-Ying; Liu, Hsin-Yu; Hsieh, Chen-Hsi (Frontiers in Pharmacology, 2020)
Background: The effects of radiotherapy (RT) on the pharmacokinetics (PK) of 5-FU and 5-fluoro-5,6-dihydro-uracil (5-FDHU) were investigated by animal experiments. Methods: Whole-pelvis RT with 0.5 and 2 Gy was delivered to Sprague–Dawley rats. 5-FU at 100 mg/kg was intravenously infused 24 hours after radiation. The pharmacokinetics of 5-FU and 5-FDHU in the plasma and bile system were calculated. Results: The areas under the concentration versus time curve (AUC) of 5-FU in the plasma were reduced by local irradiation by 23.7% at 0.5 Gy (P < 0.001) and 35.3% at 2 Gy (P < 0.001). The AUCs of 5-FDHU were also reduced by 21.4% at 0.5 Gy (P < 0.001) and 51.5% at 2 Gy (P < 0.001). Irradiation significantly increased the clearance values (CLs) of 5-FU by 30.6% at 0.5 Gy and 50.1% at 2 Gy, respectively. The CLs of 5-FDHU were increased by 27.2% at 0.5 Gy and 106% at 2 Gy. The AUCs of 5-FU in the bile were increased by 36.7% at 0.5 Gy (P < 0.001) and 68.6% at 2 Gy (P = 0.005). The AUCs of 5-FDHU in the bile were increased by 40.3% at 0.5 Gy (P < 0.001) and 248.1% at 2 Gy (P < 0.001). The CLs of 5-FU in the bile were increased by 31.8% at 0.5 Gy and 11.2% at 2 Gy. However, the CLs of 5-FDHU in the bile were decreased by 29.1% at 0.5 Gy and 71.0% at 2 Gy. Conclusion: Both conventional and low-dose irradiation can affect the pharmacokinetics of 5-FU and its metabolite, 5-FDHU. RT plus 5-FU could cause more adverse events than 5-FU alone by increasing the AUC ratio of 5-FU/5-FDHU. Irradiation decreases the AUC of 5-FU in the plasma, which may cause poor clinical outcomes.